Looking for new physics via semi-leptonic and leptonic rare decays of D and Ds - 郭星导 郝喜庆 柯红卫 赵明刚 李学潜 (中国物理C：英文版, 2017)
It is well recognized that looking for new physics at lower energy colliders is a path wnmn is complemen- tary to high energy machines such as the LHC. Using the large volume of data collected by BESIII, we may have a unique opportunity to tackle this. In this paper we calculate the branching ratios of the semi-leptonic processes D＋ → K＋e-e＋ and D＋ → K＋e-P-＋, and the leptonic processes D0→ e-e＋ and D0→ e-μ＋, in the frameworks of the U（1） model, 2HDM and unparticle model. It is found that both the U（1） model and 2HDM may influence the semi-leptonic decay rates, but only the U（1） model offers substantial contributions to the pure leptonic decays, and the resultant branching ratio of DO → e- μ＋ can be as large as 10-7 - 10-8. This might be observed at the future super τ-charm factory.